Dishevelled-1 regulates global transcriptomic changes and associates with ETS1 transcription factor - Dalia Martinez-Marin; Monica Sharma; Jenna C. van Wunnik; Flávia Sardela de Miranda; Geetha Priya Boligala; Ella C. Jull; Grace C. Stroman; Rachel L. Babcock; Kevin Pruitt (Nature Communications)
Abstract Dishevelled (DVL) is a crucial component of the Wnt-signaling pathway and is vital for multiple physiological processes. Previously thought to have a classically cytoplasmic role, the discovery of DVL nuclear translocation reframed how it is viewed functionally. Although significant progress has been made in understanding the nuclear functions of DVL, further research is required to clarify its roles in transcriptional and epigenetic regulation. A key unresolved question is whether nuclear DVL1 associates with a transcription factor partner. We show here that modulation of DVL1 expression globally affects the transcriptomic landscape. Additionally, analysis of DVL1 ChIP-sequencing allowed us to map genome-wide binding sites, revealing the extensive reach of DVL1 binding. Integration of RNA-sequencing and ChIP-sequencing further revealed ETS1 as a transcription factor binding partner which targets nuclear DVL1 to specific genomic loci. These findings provide insight into the contribution of DVL1 in transcription and clarify aspects of its elusive nuclear function.